Hospital Qualities Related to Return to Work from Occupational Injury after Controlling for Injury Severity as Well as Occupational Characteristics - Won, Jong-Uk (J Korean Med Sci, 2016)
We examined associations between hospital quality in the workers’ compensation system and injured patients’ return to work after controlling for injury severity, occupational factors, and demographic factors. Return to work data of injured workers were constructed from 2 datasets: 23,392 patients injured in 2009–2011 from the Korea Workers’ Compensation & Welfare Service and return to work data from Korea Employment Information Services. After de-identifying the data, quality scores were matched for each hospital that cared for injured patients. Injury severity was measured by Abbreviated Injury Scales. Relative risk and 95% confidence interval were calculated using log binomial regression models. After adjusting for age, sex, injury severity, occupation, factory size, city, and hospital type, the relative risk (95% confidence interval) for the total score was 1.04 (1.02–1.06), 1.06 (1.04–1.09), and 1.07 (1.05–1.10) in the 2(nd), 3(rd), and 4(th) quartiles, respectively, compared to the 1(st) quartile. The RR (95% CI) in the 2(nd), 3(rd), and 4(th) quartiles was 1.05 (1.02–1.07), 1.05 (1.02–1.08), and 1.06 (1.04–1.09) for the process score; and 1.02 (1.01–1.04), 1.05 (1.03–1.07), and 1.06 (1.04–1.09) for the outcome score compared to the 1(st) quartile score, respectively. In conclusion, our study design with blinded merge methods shows that total, process, and outcome qualities are related to the return to work of injured workers after controlling for other factors.